2022
DOI: 10.3390/ijerph19052657
|View full text |Cite
|
Sign up to set email alerts
|

Signifying the Relationship between Fear of COVID-19, Psychological Concerns, Financial Concerns and Healthcare Employees Job Performance: A Mediated Model

Abstract: The coronavirus pandemic (COVID-19) has undoubtedly created immense health problems in the global healthcare sector. Apart from its impact on physical health, it has devastatingly affected the psychological well-being of individuals. Based on Affective Events Theory (AET), the current study aims to contemplate the relationship between Fear of COVID-19 (CVF), psychological concerns (PC), and financial concerns (FC) while considering the impact on the healthcare employees’ job performance (JP). Moreover, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 110 publications
3
35
0
Order By: Relevance
“…Our results are generally in line with the majority of studies which demonstrated a significant negative impact of FCV-19 on mental health outcomes, work outcomes, quality of life, and job performance in HCWs [ 8 , 11 , 32 , 40 , 41 , 42 , 43 ]. However, the comparison of our results with those of the above studies should be considered with caution given that in many of them, FCV-19 was measured through ad hoc questions and not with validated tools.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are generally in line with the majority of studies which demonstrated a significant negative impact of FCV-19 on mental health outcomes, work outcomes, quality of life, and job performance in HCWs [ 8 , 11 , 32 , 40 , 41 , 42 , 43 ]. However, the comparison of our results with those of the above studies should be considered with caution given that in many of them, FCV-19 was measured through ad hoc questions and not with validated tools.…”
Section: Discussionsupporting
confidence: 91%
“…Fear of COVID-19 (FCV-19) has been reported to escalate faster than the virus itself, being greatly related to the uncertainties regarding the outbreak and to negatively affecting the mental state of HCWs and impeding their job performance [ 8 , 9 ]. A recent meta-review addressing the overall mental health of HCWs during the COVID-19 pandemic, identified anxiety, depression, post-traumatic stress disorder, burnout, insomnia, fear, obsessive-compulsive disorder, somatization, phobia, substance abuse, and suicidal thoughts as the most prevailing problems, especially among females and younger persons [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This shows that the five predictors (i.e., stress, depression, anxiety, job burnout, and mental health problems) accounted for 50.8% of the variance in employee performance. Overall, the R 2 values were found to meet the cut-off value of 0.30 recommended by Sarfraz [ 11 ].…”
Section: Resultsmentioning
confidence: 62%
“…The authors of one study observed that the significant repercussions of COVID-19 have damaged employees’ psychological well-being, thereby negatively impacting their normal intellectual functioning [ 9 ]. Overall, the pandemic has overwhelmed the healthcare sector by reducing employees’ work performance [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This change was from working within the organization’s physical premises to working at home—virtually. Working professionals faced different challenges caused by the pandemic, resulting in employees experiencing various psychological effects, such as high-stress levels, mental breakdowns, and depression (Chen, 2020; Sarfraz et al, 2022). Employees who managed to keep their jobs were faced with no other option but to adjust to working remotely (Carnevale & Hatak, 2020).…”
Section: Introductionmentioning
confidence: 99%